MoMkt1, a member of XPG/RAD2 nuclease family, regulates development and pathogenicity in Magnaporthe oryzae - Na Li; Junlian Xiao; Long Yan; Xiaoru Kang; Wenjuan Wang; Shen Chen; Weihuai Wu; Shulin Zhang (Virulence)
XPG/RAD2 nuclease family plays a crucial role in DNA damage repair to maintain genomic integrity. However, the biological function of Mkt1, a member of the XPG/RAD2 nuclease family, remains unclear in Magnaporthe oryzae. In this study, we identified and characterized the biological functions of MoMkt1. Our results demonstrated that MoMkt1 is involved in hyphal growth, conidiation, normal appressorium development, degradation of glycogen and lipid droplets, cell wall stress and oxidative stress responses, and pathogenicity in M. oryzae. Additionally, MoMkt1 is required for scavenging host-derived reactive oxygen species (ROS) and responding to DNA replicative stress. Further investigation revealed that MoMkt1 interacts with the transcription factor IIH (TFIIH) core subunit MoTfb2. Overexpression (OE) of MoTFB2 slightly affected the virulence of M. oryzae. Transcriptome data revealed that MoMKT1 regulates metabolic pathways, cell wall, oxidation-reduction processes, and DNA repair. Our study provides insights into MoMkt1-mediated development and pathogenicity in M. oryzae.